Impact of mineral fertilization and Trichoderma application on soil microbiota of young olive trees inoculated with Verticillium dahliae - Segarra, Guillem; Sancho-Adamson, Marc; Trillas, M. Isabel; Romanyà, Joan (Frontiers in Microbiology, 2025)
IntroductionVerticillium dahliae, the pathogen producing Verticillium wilt in olive orchards is a soilborne pathogenic fungus that has a long persistence in soil due to the formation of melanized microsclerotia and represents a devastating threat to the production in Mediterranean countries. Management of Verticillium wilt of olive is not easily achieved by means of a single treatment and thus integrated approaches are needed. Trichoderma asperellum strain T34 is a biological control agent that was isolated from a suppressive compost and has been shown to reduce the severity of various soil-borne diseases in many crops.Material and methodsTwo-year-old olive trees were planted in pots containing soil. Plants were subjected to 3 factors (fertilization, inoculation with the pathogen Verticillium dahliae and Trichoderma application) each one with two levels (yes or no), resulting in 8 groups (treatments) of plants. Soils were sampled 20 months after transplanting to perform 16S and ITS sequencing as well as to quantify the concentration of V. dahliae microsclerotia.ResultsThe treatment of the pots with the biological control agent T. asperellum strain T34 effectively reduced the amount of V. dahliae microsclerotia, suggesting a promising alternative to chemical fumigation. Moreover, it did not affect the diversity of bacteria and fungi in the rhizospheric soil of olive trees. On the other hand, mineral fertilization doubled the amount of microsclerotia in soil and drastically increased the relative abundance of V. dahliae reads. Furthermore, fertilization had a significant effect on microbial communities, mostly on bacterial populations. Interestingly, fertilization did not have an effect on the phylum Glomeromycota, and bacterial genera affected by fertilization were not specifically associated to N fixing or non-N fixing bacteria.ConclusionTaken together, those results suggest that mineral fertilization has a much more profound impact on the relative abundance of microorganisms than the introduction of biological control agents such as T. asperellum strain T34.